2017
DOI: 10.1186/s12906-017-1982-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and analgesic activities of solvent fractions of the leaves of Moringa stenopetala Bak. (Moringaceae) in mice models

Abstract: BackgroundMany people still experience pain and inflammation regardless of the available drugs for treatments. In addition, the available drugs have many side effects, which necessitated a quest for new drugs from several sources in which medicinal plants are the major one. This study evaluated the analgesic and anti- inflammatory activity of the solvent fractions of Moringa stenopetala in rodent models of pain and inflammation.MethodsSuccessive soxhlet and maceration were used as methods of extractions using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…4,26 Furthermore, polyphenols exert their anti-inflammatory properties through inhibition of the production of inflammatory cytokines and chemokine and suppressing the activity of (COX and iNOS and thereby decreasing the production of reactive oxygen and nitrogen species). 8 The results obtained from the present study were in line with the findings of others 8,9,28 that demonstrated the analgesic and anti-inflammatory activities of medicinal plants in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…4,26 Furthermore, polyphenols exert their anti-inflammatory properties through inhibition of the production of inflammatory cytokines and chemokine and suppressing the activity of (COX and iNOS and thereby decreasing the production of reactive oxygen and nitrogen species). 8 The results obtained from the present study were in line with the findings of others 8,9,28 that demonstrated the analgesic and anti-inflammatory activities of medicinal plants in a dose dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…34 This suggestion is in line with the reports that stated, phytoconstituents like, alkaloids, flavonoids, steroids, and tannin isolated from medicinal plants have been reported to possess a significant analgesic activity. 9,28 In the study of the anti-inflammatory activity, the root extract of EK was detected against carrageenan-induced acute and formalin-induced sub-acute phases of inflammation. Since the inflammatory response is a polyphasic tissue reaction, which involves both short lived increase in vascular permeability and prolonged cellular infiltration and proliferation, it is important to evaluate the potential of the extract for anti-inflammatory effect via a sequential test valid for various phases of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations